Student motivation for enrolling in public relations studies and their perception of the public relations profession and study in Croatia - Hajoš, Boris (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The number of public relations (PR) students has been steadily rising in Croatia and so is the number of high schools teaching PR. The aim of this research was to learn about what motivates students to study PR and to explore their perception of the PR profession and the PR study. The survey was conducted online in October 2016 with 383 respondents: first year students, senior students and graduate students at undergraduate and graduate PR studies in Croatia. The respondents’ common motive for enrolling PR studies is an interesting and creative curriculum, followed by personal interest and desire to work in PR and the attractiveness of the work in PR. The most desired jobs are in corporate communication and the participants were the most interested in event management, product promotion, media relations and internal communication. Seven in ten respondents said that a PR degree would help them to find a job in the profession, while 60% responded that PR experts are a profession sought after in the labour market. Essential for getting a job in the profession are work experience in PR, informal knowledge and skills, relationships and acquaintances and formal knowledge taught at university. The majority of respondents (87%) were satisfied with their selected studies, and they gave it a very good mark. Senior students believe that their studies gave them good communication skills, teamwork skills, good writing and reading, and less computer skills, analytical and problem solving skills, and foreign languages. Everyone in eight students of private universities experienced discrimination in recruitment process.